EFEKTIVITAS PENGELOLAAN DANA BPIH TERHADAP PERSPEKTIF EKONOMI ISLAM PADA PEMBIAYAAN HAJI (STUDI KASUS: NASABAH HAJI SOLO BARU) - Shifa Barirohtun, Annasza; Januar Rivtia, Intan; Nayotama Yasir, Mahatva; Waluyo, Waluyo (JISEF : Journal Of International Sharia Economics And Financial, 2025)
In the implementation of the Hajj, there are various aspects that need to be fulfilled by the managing party (government) such as the transportation, consumption, and health sectors. Likewise, from the side of the Hajj pilgrims themselves, such as fulfilling the BPIH (Hajj Pilgrimage Organization Costs), as well as the completeness of the files. Therefore, where the implementation of the Hajj can be carried out properly and the funds needed are in accordance with the security of the needs of the Hajj pilgrims, a Hajj Pilgrimage Organization Cost fund management system is needed that is in accordance with existing procedures. This study aims to analyze whether the effectiveness of good BPIH fund management can affect the implementation of the Hajj pilgrimage for pilgrims with a qualitative method approach. Where this study uses literature studies from journal sources and previous research. The results of this study indicate that the effectiveness of BPIH fund management can improve the quality of service and satisfaction of pilgrims. Through good management, BPIH funds can provide positive effects such as reducing costs, improving services, and ensuring the safety and comfort of pilgrims.